The effectiveness of Online Structured Inquiry Learning (OSIL) in building and seeking certainty of hypotheses based on Citizenship and Civic Values / Mohd Razimi Husin ... [et al.] - Husin, Mohd Razimi; Ahmad, Hishamuddin; Abdul Majid, Norliza (2021)
A study in Peninsular Malaysia found that the involvement of students in citizenship education classroom activities was moderate with a mean of 2.99 causing the objectives of the activities to achieve less real goals. In-country research on the Elements of Citizenship and Civic Values is very poorly implemented. Overseas studies found that adolescents' nationalism towards the country was at a low level with 45.83%. There are still teenagers who cheat, don’t follow rules and are undisciplined. Therefore, a study needs to be implemented to form an Online Structured Inquiry Learning based on the Elements of Citizenship and Civic Values in the subject of History. This study uses an intervention of quasi-experiment design. Online Structured Inquiry Learning (OSIL) is an independent variable. Two dependent variables are first, the ability to construct the Citizenship Element and Civic Values hypothesis, and second, the ability to find certainty of the Citizenship Element and Civic Value hypothesis. A total of 20 form 1 students in schools in Peninsular Malaysia have been selected through non-random and purposeful sampling. Evaluation of the effectiveness of dependent variables using test data after the intervention. The instruments used in the test were analysed manually to obtain the mean of the two methods used for comparison. The results of the study found that the mean of appreciation of the elements of citizenship and civic values was higher with an average mean of 2.0 using OSIL compared to 1.08 teaching without OSIL. This study produces a kit to guide teachers to form citizens who have a Malaysian identity and personality. This learning framework is contributing to History teachers, especially as a teaching reference in fulfilling national aspirations through the application of patriotic attitudes and positive values based on the principles of Rukun Negara and based on the National Constitution.